Comparisons of observed and modeled elastic responses to hydrological loading in the Amazon basin. Issue 18 (29th September 2016) - Moreira, D. M.; Calmant, S.; Perosanz, F.; Xavier, L.; Rotunno Filho, O. C.; Seyler, F.; Monteiro, A. C.
Abstract: In large hydrological basins, water mass loading can produce significant crustal deformation. We compare the monthly vertical component of 18 GPS sites located in the Amazon basin, with the deflection models derived from Gravity Recovery and Climate Experiment (GRACE) observations on the one hand and derived from HYDL, a global hydrological model, on the other hand. The GPS data set includes the largest deflections by hydrological loading ever recorded at two stations located in the center of the basin. The main result of the study is that the GRACE solution produced by GRGS (Groupe de Recherche en Géodesie Spatiale, Toulouse, France) produces the best agreement with the Global Navigation Satellite Systems series with a correlation coefficient up to 0.9 in the center of the basin, although 70% at best of the RMS variation in the GPS series is accounted for. Key Points: Crustal displacements derived from GRACE and hydrological models Vertical component of GPS time series over the Amazon basin Historical flood and drought in the Amazon basin